KUALITAS GURU SEJARAH DALAM PROSES BELAJAR ENGAJAR DITINJAU DARI ASPEK PEMBELAJARAN STUDI KASUS MAN 2 BANYUWANGI - Ahmad Rofi’i; Agus Mursidi (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2018)
History Learning in Senior High Schools or Islamic Senior High Schools. Case study at MAN 2 Banyuwangi. Aim to take a picture and describe about (1) History Teacher's competency and Quality, (2) implementation of historical learning in MAN 2 Banyuwangi, (3) constraints and efforts faced by history teachers in implementing learning. This research was conducted in the 2018 school year at MAN 2 Banyuwangi. The research method used is a descriptive qualitative method in the form of a case study. The informants from this study were history teachers and students. The sampling technique is done by purposive sampling. In order to ensure the stability and correctness of the data collected, the data validity was carried out, in this study carried out by the Trianggulation Technique method (interviews, observation, questionnaires, and recording documents). Data collection is done by in-depth interviews, observations, quizisoner techniques, and recording documents. Data analysis techniques use an interactive analysis model.